Planificación tributaria de empresas de seguridad privada, y sus efectos en el capital de trabajo - Buendía Noroña, Andrés Santiago (2025)
The objective of this study, "ACCOUNTING AND TAX MANAGEMENT FOR PRIVATE SECURITY COMPANIES", was to analyze the management of the accounting control of non-deductible expenses and the recovery of the tax credits of the companies, these being the withholdings at the source and the VAT withholdings, and how these affect the reasonableness of the financial statements, in particular the statement of comprehensive income, which was developed based on a methodological process, which began with the identification of the mixed approach, as well as the type of investigation, this being the descriptive one, where the current situation of the processes maintained by companies in the private security sector was analyzed, diagnosed and interpreted, identifying factors that influence the verification process with the reality of the comprehensive income statements of the company, for this, a research instrument was applied, being the interview, which helped to collect are information, the same that generated results focused on accounting control management.